When Age and Culture Interact in an Easy and Yet Cognitively Demanding Task: Older Adults, But Not Younger Adults, Showed the Expected Cultural Differences - Na, Jinkyung; Huang, Chih-Mao; Park, Denise C. (Frontiers in Psychology, 2017)
The interaction between age and culture can have various implications for cognition as age represents the effect of biological processes whereas culture represents the effect of sustaining experiences. Nevertheless, their interaction has rarely been examined. Thus, based on the fact that Asians are more intuitive in reasoning than Americans, we examined how this cultural difference might interact with age. Young and old participants from the US and Singapore performed a categorization task (living vs. non-living). To measure their reliance on intuition, we manipulated the typicality of targets (animate vs. inanimate). We showed that (1) RTs for inanimate organisms were slower than RTs for animate organisms (atypicality cost), (2) the cost was particularly large for older adults and (3) an age × culture interaction was observed such that cultural differences in the cost (Singaporeans > Americans) was found only among older participants. Further, we demonstrated that the age effect was associated with cognitive function and the culture effect among older adults was associated with cultural values. Finally, a moderated mediation analysis suggests that cognitive function and cultural values interact with each other in order to jointly influence one’s cognition.